Global guide of the flat wasps (Hymenoptera, Bethylidae) - Azevedo, Celso O.; Alencar, Isabel D.c.c.; Ramos, Magno S.; Barbosa, Diego N.; Colombo, Wesley D.; Vargas, Juan M. R.; Lim, Jongok (Zootaxa, 2018)
The flat wasp family Bethylidae Haliday lacks global scale literature on their alpha taxonomy. The only world revision for the family was by Kieffer in 1914 and is fully out of date and somewhat useless; the only catalog for the family was made by Gordh & Móczár in 1990 and does not include hundreds of changes made since then; and the most recent world genera keys were proposed by Terayama in 2003, but do not reflect the current knowledge we have for the family. Given this scenario, we present a global guide of Bethylidae with diagnoses, taxonomic evaluation, keys, and a checklist of all their extant genera and subfamilies. We visited the main collections around the world, analyzed about 2,000 holotypes, and examined at least 400,000 specimens. To eliminate homonymies, we add the prefix “neo” to the original specific epithet when possible. The family is now composed by 2,920 species allocated in 96 genera distributed in eight subfamilies: Bethylinae, Pristocerinae, Epyrinae, Mesitiinae, Scleroderminae, Lancepyrinae, Holopsenellinae and Protopristocerinae. The latter three are extinct. One new family-group synonym is proposed: Fushunochrysidae Hong syn. nov. of Bethylidae. Two incertae sedis genera are allocated into Bethylinae: Cretobethylellus Rasnytsyn and Omaloderus Walker. One new genus-group synonym is revalidated: Pristepyris Kieffer stat. rev. from Acrepyris Kieffer. Sixteen new genus-group synonyms are proposed: Fushunochrysites Hong syn. nov. and Sinibethylus Hong syn. nov. of Eupsenella Westwood; Messoria Meunier syn. nov. of Goniozus Förster; Acrepyris Kieffer syn. nov. of Pristepyris Kieffer; Apristocera Kieffer syn. nov. and Parapristocera Brues syn. nov. of Pristocera Klug; Usakosia Kieffer syn. nov. of Prosapenesia Kieffer; Isobrachium Förster syn. nov., Leptepyris Kieffer syn. nov., Neodisepyris Kurian syn. nov., Rhabdepyris Kieffer syn. nov. of Epyris Westwood; Codorcas Nagy syn. nov., Hamusmus Argaman syn. nov. and Ukayakos Argaman syn. nov. of Heterocoelia Dahlbom; Domonkos Argaman syn. nov. of Incertosulcus Móczár; Ateleopterus Förster syn. nov. of Sclerodermus Latreille. One new genus-group synonym is revalidated: Topcobius Nagy syn. rev. of Sulcomesitius Móczár. One new genus-group revalidation is proposed: Incertosulcus Móczár stat. rev. from Anaylax Móczár. The following species-group nomenclatural acts are established: 153 new or revalidated combinations, 16 new names to avoid secondary homonyms, 11 species with revalidated status, and one synonym. Keys to the subfamilies and genera are provided. The text is supported by 599 illustrations organized onto 92 plates.